2020
DOI: 10.1101/2020.02.25.964890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual Experience is not Necessary for the Development of Face Selectivity in the Lateral Fusiform Gyrus

Abstract: Here we show robust face-selectivity in the lateral fusiform gyrus of congenitally blind participants during haptic exploration of 3D-printed stimuli, indicating that neither visual experience, nor fovea-biased input, nor visual expertise is necessary for face-selectivity to arise in its characteristic location. Similar resting fMRI correlation fingerprints in individual blind and sighted participants suggest a role for long-range connectivity in the specification of the cortical locus of face-selectivity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Importantly, we also showed that EBA, WFA and NFA in the blind brain were functionally connected to other main regions forming the typical network of processing for body-shapes (Striem-Amit and Amedi, 2014), letters, and numbers (Abboud et al, 2015), respectively. Finally, most recently, we reported similar results also for SSD perceived faces in the Fusiform Face Area (FFA) ( (Arbel et al, 2020) see also (Murty et al, 2020) for converging results obtained in touch). We showed that after ∼12 h of face dedicated training, blind-from-birth adults expert SSD users, recruited a region in the Fusiform Gyrus in an anatomical location compatible with FFA (both at the group and at the individual levels), alongside other regions known to be involved in face processing such as the Occipital Face Area (OFA).…”
Section: Computation-based Sensory-independent Cortical Organizationsupporting
confidence: 70%
“…Importantly, we also showed that EBA, WFA and NFA in the blind brain were functionally connected to other main regions forming the typical network of processing for body-shapes (Striem-Amit and Amedi, 2014), letters, and numbers (Abboud et al, 2015), respectively. Finally, most recently, we reported similar results also for SSD perceived faces in the Fusiform Face Area (FFA) ( (Arbel et al, 2020) see also (Murty et al, 2020) for converging results obtained in touch). We showed that after ∼12 h of face dedicated training, blind-from-birth adults expert SSD users, recruited a region in the Fusiform Gyrus in an anatomical location compatible with FFA (both at the group and at the individual levels), alongside other regions known to be involved in face processing such as the Occipital Face Area (OFA).…”
Section: Computation-based Sensory-independent Cortical Organizationsupporting
confidence: 70%
“…46 As further evidence for connectivity from non-visual areas, the putative VWFA has stronger functional correlations with putative language areas compared to functional correlations between nearby FFA and putative language areas. 47 Finally, congenitally blind humans have auditory and tactile responses in the FFA that are selective for faces 48,49 and distinctive patterns of resting functional correlation between the ''blind FFA'' and both visual and non-visual regions. 48 Thus, we speculate that the location of FFA, PPA, and EBA may be influenced by preexisting long-range connectivity to both early visual regions and also regions in parietal and frontal cortex.…”
Section: Articlementioning
confidence: 99%
“…47 Finally, congenitally blind humans have auditory and tactile responses in the FFA that are selective for faces 48,49 and distinctive patterns of resting functional correlation between the ''blind FFA'' and both visual and non-visual regions. 48 Thus, we speculate that the location of FFA, PPA, and EBA may be influenced by preexisting long-range connectivity to both early visual regions and also regions in parietal and frontal cortex.…”
Section: Articlementioning
confidence: 99%
“…However, previous research demonstrated that even third‐trimester fetuses respond preferentially to face‐like configurations (Reid et al., 2017; Ronga et al., 2018) and that newborns are endowed with a cortical network specific for the elaboration of such configurations (Buiatti et al., 2019). These findings, together with further evidence highlighting a similar preference for face‐like configurations also in other species (Nguyen et al, 2013; Salva et al, 2011) and revealing cortical face‐specific responses also in absence of visual experience (Ratan Murty et al, 2020), suggest that faces and face‐like configurations might have a sort of “innate” evolutionary salience for the nervous system. This salience might result in the enhanced processing of such specific visual configurations per se, independently from their semantics, which can be acquired only later in ontogenesis.…”
Section: Discussionmentioning
confidence: 56%